2019
DOI: 10.1182/bloodadvances.2019000621
|View full text |Cite
|
Sign up to set email alerts
|

Smooth muscle cytochrome b5 reductase 3 deficiency accelerates pulmonary hypertension development in sickle cell mice

Abstract: Key Points Vascular SMC CYB5R3 delays development of SCD-associated PH in mice. PH in SCD can exist in mice by 5 weeks of age when SMC CYB5R3 protein is deficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
(85 reference statements)
0
12
0
Order By: Relevance
“…Experiments with the purified proteins showed that CYB5R3 was able to reduce the sGC ferric heme, albeit slowly, in a reaction that depended on NADPH and a direct protein–protein interaction ( 93 ). In a mouse model of sickle cell disease, CYB5R3 knockdown also enhanced the development of NO insensitivity of vascular sGC ( 121 ). Together, these findings argue that sGC heme oxidation occurs in oxidative or inflammatory settings and that heme reduction mediated by CYB5R3 is functionally significant for sGC recovery of function.…”
Section: Recovery Of Inactive Sgcmentioning
confidence: 99%
“…Experiments with the purified proteins showed that CYB5R3 was able to reduce the sGC ferric heme, albeit slowly, in a reaction that depended on NADPH and a direct protein–protein interaction ( 93 ). In a mouse model of sickle cell disease, CYB5R3 knockdown also enhanced the development of NO insensitivity of vascular sGC ( 121 ). Together, these findings argue that sGC heme oxidation occurs in oxidative or inflammatory settings and that heme reduction mediated by CYB5R3 is functionally significant for sGC recovery of function.…”
Section: Recovery Of Inactive Sgcmentioning
confidence: 99%
“…1 ). Recent evidence has shown that oxidative stress associated with many cardiopulmonary diseases shifts intracellular native sGC levels towards the apo-sGC form [ 47 , 48 ], providing the rationale for sGC activators [ 49 52 ] in cardiopulmonary diseases and PH.…”
Section: Discussionmentioning
confidence: 99%
“…Results show percentage changes versus vehicle-treated control animals as mean ± SEM out of three or four experiments. BP mean blood pressure, PAP mean pulmonary arterial pressure, SEM standard error of the mean sGC levels towards the apo-sGC form [47,48], providing the rationale for sGC activators [49][50][51][52] in cardiopulmonary diseases and PH.…”
Section: Discussionmentioning
confidence: 99%
“…CYB5R3 supports NO-responsive sGC by reducing its ferric heme to ferrous [ 32 ]. When CYB5R3 expression was knocked down in cells or in mice, their sGC became more susceptible to oxidative stressors causing NO-insensitivity and led to a greater BAY-60 activation response [ 45 ]. In our study, we found a strong correlation exists between low levels of CYB5R3 expression and sGC dysfunction in the HASMC lines and lung tissues.…”
Section: Discussionmentioning
confidence: 99%